2021
DOI: 10.1159/000512000
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Nivolumab in Renal Cell Carcinoma: A Real-World Experience

Abstract: <b><i>Background:</i></b> The approved doses of the single agent nivolumab – an anti-programmed cell death protein 1 (PD-1) monoclonal antibody – for renal cell carcinoma (RCC) are 3 mg/kg and a 240-mg flat dose, despite efficacy shown at lower doses in earlier CheckMate trials. In view of financial constraints, the minimum dose of nivolumab required for efficacy remains a critical area of inquiry. <b><i>Methods:</i></b> A retrospective review of RCC patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…The development of generic or bio-similar molecules and innovative studies on low-dose regimens or longer duration treatment schedules would help bring down the cost of treatment and improve accessibility in these regions. There are multiple retrospective analyses that suggest that such schedules might be helpful [26][27][28]. However, there is need for performing dose response, minimum effective dose finding studies and these need to be backed up by phase 2 and phase 3 randomised studies.…”
Section: Discussionmentioning
confidence: 99%
“…The development of generic or bio-similar molecules and innovative studies on low-dose regimens or longer duration treatment schedules would help bring down the cost of treatment and improve accessibility in these regions. There are multiple retrospective analyses that suggest that such schedules might be helpful [26][27][28]. However, there is need for performing dose response, minimum effective dose finding studies and these need to be backed up by phase 2 and phase 3 randomised studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study confirmed similar efficacy and safety between a flat dose of 240 mg nivolumab and a dose of 3 mg/kg nivolumab based on pharmacokinetic and dose efficacy analyses, indicating that a lower flat dose nivolumab (20 or 100 mg) might be comparably effective to a higher dose [28]. Therefore, growing evidence has confirmed the efficacy and safety of low-dose ICIs to reduce the financial toxicity and improve clinical outcome in several cancer types, such as NSCLC, RCC, and Hodgkin lymphoma [15][16][17]. In NSCLC, Yoo et al reported 47 patient who received low-dose nivolumab (20 or 100 mg) or standard dose (3 mg/kg) for cancer treatment; there was no statistical difference of ORR (13.8% versus 16.7%), PFS (3.0 month versus 1.0 month) and OS (12.5 month versus 8.2 month) between low-dose group and standard dose groups [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lowdose ICIs may be a viable option for the management of cancer. Growing evidence has demonstrated the efficacy of low-dose nivolumab in some cancer types, such as NSCLC, recall cell carcinoma (RCC), and Hodgkin lymphoma [15][16][17]. The major rationale is that no correlation between dose and response has been observed for anti-PD-1 ICIs, whether nivolumab or pembrolizumab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study from Korea compared the low-dose nivolumab group (20 mg/100 mg Q3W) with the standard-dose group (3 mg/kg Q2W) in nonsmall cell lung cancer (NSCLC) with no significant difference in ORR, progression-free survival (PFS), and overall survival (OS) (34). Results from another retrospective studies in Singapore also showed that low-dose (100 mg/140 mg) nivolumab did not reduce efficacy in renal cancers (35). In a single-arm, open-label phase II study conducted in Russia, the ORR for 40 mg Q2W nivolumab in relapsed/refractory Hodgkin lymphoma was 70%, with 13/30 (43.3%) achieving complete remission (CR) (36).…”
Section: Nivolumabmentioning
confidence: 99%